3D Radiological Evaluation of Upper Central Incisors and Canines Development in Patients with Unilateral Cleft Lip and Palate (Journal of Hama University, 2024)
The aim of this study is to evaluate dental development of cleft-side anterior upper teeth compared with the contralateral teeth in patients with unilateral cleft lip and palate (UCLP) using cone beam computed tomography (CBCT).: Retrospective database of 32 Cone beam computed tomography scans of patients with unilateral cleft lip and palate (mean age = 10.53 ± 1.51 years) were assessed. The data for upper central incisors and canines adjacent to the cleft were compared with those of contralateral non-cleft teeth. For each tooth analyzed, root length (RL), crown height (CH) and root length to crown height ratio (R/C) were measured using Invivo6 software.The root length, crown height and R/C ratio of upper central incisors on cleft side were significantly less than their contralateral antimeres (P < 0.001, P = 0.013 and P = 0.001, respectively). For upper canines, the root length and R/C ratio of those on cleft side were significantly less than those in non-cleft side (P = 0.018 and P = 0.011, respectively). There was no statistically significant difference in crown height of upper canines between sides (P = 0.500).Patients with unilateral cleft lip and palate demonstrated a significant deficiency in root and crown development of central incisors on cleft side compared with their contralateral antimeres, with the root affected most severely. Upper canines on cleft side demonstrated deficiency only in root development. Therefore, upper cleft-side central incisors were more severely affected than canines.
Keywords: Cleft Lip and Palate – Root Length – Crown Height – Cone Beam Computed Tomography.